Conflict, politics and proselytism Methodist missionaries in colonial and postcolonial Upper Burma, 1887-1966 - Leigh, Michael D. (Studies in imperialism, 2011)
An exploration of Methodist missionaries working in Upper Burma between 1887 and 1966